A Look from the Inside: MicroCT Analysis of Burned Bones - Francesco Boschin; Clément Zanolli; Federico bernardini; Francesco Princivalle; Claudio Tuniz (Ethnobiology Letters, 2015)
MicroCT imaging is increasingly used in paleoanthropological and zooarchaeological research to analyse the internal microstructure of bone, replacing comparatively invasive and destructive methods. Consequently the analytical potential of this relatively new 3D imaging technology can be enhanced by developing discipline specific protocols for archaeological analysis. Here we examine how the microstructure of mammal bone changes after burning and explore if X-ray computed microtomography (microCT) can be used to obtain reliable information from burned specimens. We subjected domestic pig, roe deer, and red fox bones to burning at different temperatures and for different periods using an oven and an open fire. We observed significant changes in the three-dimensional microstructure of trabecular bone, suggesting that biomechanical studies or other analyses (for instance, determination of age-at-death) can be compromised by burning. In addition, bone subjected to very high temperatures (600°C or more) became cracked, posing challenges for quantifying characteristics of bone microstructure. Specimens burned at 600°C or greater temperatures, exhibit a characteristic criss-cross cracking pattern concentrated in the cortical region of the epiphyses. This feature, which can be readily observed on the surface of whole bone, could help the identification of heavily burned specimens that are small fragments, where color and surface texture are altered by diagenesis or weathering.